Non-Tariff Barriers and the Telecommunications Sector - Sherry M. Stephenson (Hamburg Institute of International Economics (HWWA), 2002)
This paper discusses the nature, importance, and measurement of non-tariff barriers (NTBs) in services trade with particular reference to telecommunications services. It is shown that although more effectively addressed for the telecom sector at the multilateral level than for other service sectors, NTBs are still widespread and would appear to have a large potential for restricting trade in services. The paper reviews the scope and classification of non-tariff barriers to services trade and sets out an alternative typology for their classification, highlighting the fact that NTBs may be either government-imposed, may result from non-competitive market structures, or from the absence of appropriate regulation. The latter is shown to constitute one of the most important sources of NTBs in network industries, such as telecommunications services. Attempts by the relevant literature to measure NTBs in telecommunications are summarized and their usefulness in identifying ?appropriate? policy mixes is commented. Lastly, the paper probes the question of whether existing multilateral and regional instruments and agreements are adequate to deal with the non-tariff phenomenon in the telecom sector in its several dimensions. – – 7 Dieses Papier behandelt das Wesen, die Bedeutung und die Messung nicht-tarifärer Handelsbeschränkungen (NTBs) im Dienstleistungshandel, unter besonderer Berücksichtigung der Telekommunikationsdienstleistungen. Es zeigt, dass NTBs, obwohl sie in der Telekommunikation auf der multilateralen Ebene wirksamer angegangen wurden als in anderen Dienstleistungsbereichen, noch immer weit verbreitet sind und den Dienstleistungshandel potentiell stark beeinträchtigen. Das Papier beschreibt die Erscheinungsformen und die Klassifikation nicht-tarifärer Handelsschranken im Dienstleistungshandel. Es stellt ein alternatives Klassifikationsschema vor, das von der Beobachtung ausgeht, dass NTBs entweder von Regierungen eingeführt sein können, oder auf monopolistischen Marktstrukturen basieren, oder Ergebnis unzureichender Regulierungen sind. Gezeigt wird, dass der letztgenannte Tatbestand eine der wichtigsten Quellen von NTBs in Netzwerkindustrien, wie der Telekommunikation, ist. Das Papier gibt einen Überblick über die Literatur zur Messung nicht-tarifärer Handelsschranken in der Telekommunikation und kommentiert ihre Brauchbarkeit für die Entwicklung geeigneter ?policy mixes?. Schließlich wird geprüft, ob die existierenden multilateralen und regionalen Instrumente und Vereinbarungen ausreichend sind, um mit dem vielschichtigen Problem der nicht-tarifären Hemmnisse im Telekommunikationssektor umzugehen.
Keywords: F13; F02; L96; 330; International Economic Order; Trade Negotiations; Non-Tariff Barriers; Telecommunications Services; Telekommunikation; Internationaler Dienstleistungsverkehr; Nichttarifäre Handelshemmnisse; Network Externalities; Welt